PENGARUH MODEL PEMBELAJARAN COOPERATIVE TIPE TEAMS GAMES TOURNAMENT TERHADAP HASIL BELAJAR PKN PESERTA DIDIK KELAS IV SD NEGERI 20 INDARUNG KOTA PADANG - Anisa Miftahul Janah; Merri Yelliza (Jurnal Riset Pendidikan Dasar Dan Karakter, 2025)
This study aims to determine the effect of the cooperative learning model of Teams Games Tournament (TGT) on the Civic Education learning outcomes of fourth-grade students at SD Negeri 20 Indarung, Padang City. This study was motivated by the low Civic Education learning outcomes caused by learning activities that were still dominated by the lecture method, making students less active. This research used a quantitative approach with a quasi-experimental design and a posttest-only control group design. The sample consisted of 58 students, including class IVA as the control class and class IVB as the experimental class. The sampling technique used was saturated sampling. The research instrument was a multiple-choice test. Data were analyzed using normality tests, homogeneity tests, and an independent sample t-test. The results showed that the average posttest score of the experimental class was 85.86, while the control class was 63.07. The t-test result showed that tcount = 9.038 > ttable = 1.673. Therefore, the TGT model had a significant effect on students’ Civic Education learning outcomes.